Current Trends in Web Engineering : 15th International Conference, ICWE 2015 Workshops, NLPIT, PEWET, SoWEMine, Rotterdam, The Netherlands, June 23-26, 2015. Revised Selected Papers - Daniel, Florian; Diaz, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of Current Trends in Web Engineering, ICWE Workshops 2015 which was held in June 2015 in Rotterdam, The Netherlands. The 16 revised full papers were selected form 23 submissions and cover topics on natural language processing for informal text, pervasive Web technologies, trends and challenges, and mining in the social Web.
Natural Language Processing for Informal Text -- Pervase WEb Technologies -- Mining the Social Web.
Keywords: Information storage and retrieva; Data mining; Software engineering; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Software Engineering